Effect of a Novel Betel Leaf Dentifrice on Commonly Seen Oral Hygiene Parameters-A Randomized Clinical Crossover Study - Maha Ziad Ali; Wafaa Fathy Ahmed Elbaz; Saja Adouri; Vijay Desai; Salem Abu Fanas; Biju Thomas; Sudhir Rama Varma (MDPI AG, 2022)
The use of herbal medicine in dentistry has grown exponentially over time. Currently, herbal medicine is considered an effective oral hygiene aid. The objective of the current study is to assess the anti-plaque efficiency and reduction of gingival bleeding of betel leaf and miswak (Salvadora persica) toothpaste. This randomized clinical cross-over pilot study enrolled 60 individuals with mild gingivitis. They were segregated into two groups by drawing lots. The study lasted 20 days and included a two-week washout period between miswak and betel leaf toothpaste. The gingival and plaque index were measured at specific time intervals during the research period. The results revealed that betel leaf and miswak herbal toothpaste significantly decreased plaque index. Nevertheless, betel leaf toothpaste caused a more significant reduction in gingival bleeding scores (p < 0.001) when compared to miswak (p = 0.007). No significant decrease in gingival and plaque index was seen when subjects were asked to return to their conventional chemical toothpaste. The current study concluded that betel leaf toothpaste displayed a more substantial decrease in gingival bleeding when compared to miswak toothpaste. Additionally, more studies should be done on the therapeutic benefits of betel leaf toothpaste.